KINERJA PEGAWAI DALAM MEMBERIKAN PELAYANAN DIKANTOR KELURAHAN KOTA TINGGI KECAMATAN PEKANBARU KOTA (STUDI KASUS: PELAYANAN UMUM) - Damanik, Dinda Aldina; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Kelurahan kota tinggi office is a government agency or public organizations in the implementation refers to standardization in the service of showing the duties and function of each part that is in the kelurahan kota tinggi . as a government agency that includes the human resources that employees who work at the institution. Lurah Kota Tinggi implement development programs work performance of employees. However, if viewed directly in the field then there's also a mismatch with their responsibilities. The work should be completed in a short time could be delayed, employee professionalism in providing services to the community is still poor and own problems that occurred. In determining the informants in this study , named employees of the Kelurahan Kota Tinggi used as informants by simple random . In accordance with the purpose of research which has been mentioned above, the necessary data , including primary data and secondary data . The concept of the theory used in this study uses the theory of Bernardin and Russel . There are six indicators to look at the performance of the Kelurahan Kota Tinggi. That is: The quality of work , quantity of work , timeliness , effectiveness , independence and work commitments . For the technique of data collection was done by interview , observation and literature study . Methods of data analysis used in this study is a qualitative descriptive analysis . These results indicate that the district office performance Kota Tinggi still not working optimally. Still, there are employees who work not in accordance with its function and follow the vision and mission of the Kelurahan Kota Tinggi. Kelurahan kota tinggi employees also have the ability / level of education that is not in accordance with the job description. Required training for office workers to enhance the performance and capabilities kota tinggi district office employees to comply with the District of Mission Vision Kota Tinggi. Keyword : Perfomance, employees, and public service